Calling by domestic piglets during simulated crushing and isolation: a signal of need - Illmann, Gudrun; Hammerschmidt, Kurt; Spinka, Marek; Tallet, Céline (PLoS One, 2013)
This study examined whether piglet distress vocalizations vary with age, body weight and health status, according to the predictions of the honest signalling of need evolutionary model. Vocalizations were recorded during manual squeezing (a simulation of being crushed by mother sow) and during isolation on Days 1 and 7 after birth in piglets from 15 litters. We predicted that during squeezing, younger, lighter and sick piglets would call more intensely because they are in higher risk of dying during crushing and therefore they benefit more from the sow's reaction to intensive vocalization. For isolation, we predicted that lighter and younger piglets would call more because they are more vulnerable to adverse effects of the separation. Calls were analyzed in their time and frequency domain. The rate of calling, call duration, proportion of high-pitched calls and eight acoustic parameters characterizing frequency distribution and tonality were used as indicators of acoustic signalling intensity. Piglets that experienced "squeezing" on Day 1 produced more intense acoustic distress signalling than on Day 7. Lighter piglets called more during squeezing than heavier piglets. Health status did not significantly affect any of the indicators of intensity of vocalization during squeezing. In isolation, none of the parameters of vocalization intensity were affected either by the age or by the weight of the piglets. In summary, the model of honest signalling of need was confirmed in the squeezed situation, but not in the isolation situation.
Keywords: stárnutí; Swine; prasata; nemoci prasat; zvířata; ženské pohlaví; Female; mužské pohlaví; Aging; Male; Animals; rány a poranění; Wounds and Injuries; Vocalization, Animal; Swine Diseases; vokalizace zvířat; Behavior, Animal; chování zvířat